2000
DOI: 10.1021/bi0001271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rett Syndrome Mutations of the Methyl-CpG Binding Domain of the Transcriptional Repressor MeCP2 on Selectivity for Association with Methylated DNA

Abstract: We have investigated the properties of mutant forms of the methyl-CpG binding transcriptional repressor MeCP2 associated with Rett syndrome, a childhood neurodevelopmental disorder. We find that four Rett syndrome mutations at known sites within the methyl-CpG binding domain (MBD) impair binding to methylated DNA, but have little effect on nonspecific interactions with unmethylated DNA. Three of these mutations (R106W, R133C, and F155S) have their binding affinities for methylated DNA reduced more than 100-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 21 publications
9
101
1
1
Order By: Relevance
“…The properties of a subset of these mutations have been examined. In the context of Xenopus MeCP2, missense mutations in the MBD domain (R106W, R133C, F155S, and T158M) reduced the ability of the protein to bind methylated DNA (Ballestar et al, 2000). Selective binding was essentially eliminated in all the mutants examined with the exception of T158M, which reduced binding a nity by a factor of two (Ballestar et al, 2000).…”
Section: Rett Syndrome and Mecp2mentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of a subset of these mutations have been examined. In the context of Xenopus MeCP2, missense mutations in the MBD domain (R106W, R133C, F155S, and T158M) reduced the ability of the protein to bind methylated DNA (Ballestar et al, 2000). Selective binding was essentially eliminated in all the mutants examined with the exception of T158M, which reduced binding a nity by a factor of two (Ballestar et al, 2000).…”
Section: Rett Syndrome and Mecp2mentioning
confidence: 99%
“…In the context of Xenopus MeCP2, missense mutations in the MBD domain (R106W, R133C, F155S, and T158M) reduced the ability of the protein to bind methylated DNA (Ballestar et al, 2000). Selective binding was essentially eliminated in all the mutants examined with the exception of T158M, which reduced binding a nity by a factor of two (Ballestar et al, 2000). An analysis of Rett mutants in the context of the MBD domain of rat MeCP2 revealed that the missense mutants R106W, R133C and F155S have a signi®cant e ect on DNA binding a nity (Free et al, 2000).…”
Section: Rett Syndrome and Mecp2mentioning
confidence: 99%
“…The conserved arginine at the analogous position in MBD1 forms a hydrogen bond with the guanine base and forms part of the hydrophobic pocket into which the methyl group of 5-methylcytosine nestles (27). Mutation of this arginine to cysteine dramatically impairs selective recognition of methylated DNA by human, rat, and Xenopus MeCP2 (12,28,29). A recombinant version of the human MeCP2(R133C) mutant was expressed and purified from bacteria as described for the wild-type protein.…”
Section: Mecp2mentioning
confidence: 99%
“…It 441 has been suggested that the hydrophobic residues placed in the hairpin loop play a role in stabilizing the orientation of the hairpin relative to the rest of the molecule (20). Mutant T158M-MBD was proven to have only a two-fold decrease of its selectivity for methylated DNA compared with the wild-type MECP2 (14).…”
Section: Resultsmentioning
confidence: 99%
“…Missense mutations identified in MECP2 in patients with RTT were found in the functional domains, MBD and TRD, but also in the C-terminus region. In vitro studies have demonstrated that many missense mutations within the MBD have a significant impact on the affinity of MECP2 for methylated DNA (14). This function is retained if the mutation affects TRD, but the ability of MECP2 to repress transcription is impaired (15).…”
Section: Introductionmentioning
confidence: 99%